Communication, education and information about coronavirus disease (COVID-19) online through the Whatsapp group network - Azmiyannoor, Muhammad (BKM Public Health and Community Medicine, 2021)
Objective: The purpose of this study was to determine changes in respondents' knowledge regarding Covid-19 before and after being given communication, information, and education. Method: This study uses a pre-experimental design with the type of one-group pre-post test design. The target of this activity is the general public who are willing to take part in educational activities and join Whatsapp groups created by volunteers from students of the Public Health Study Program, Faculty of Medicine, Lambung Mangkurat University. The number of participants in the activity was 1,622 people who were divided into 54 Whatsapp groups. Participants of the activity received intervention related to efforts to prevent Covid-19. The data were analyzed statistically with a p-value of 0.05. Results: The results of the analytical knowledge test on prevention, transmission, early detection, symptoms, and status of Covid-19 patients before and after counseling were as follows: p-value = 0.227, 0.109, 0.000, 0.000, and 0.000. Conclusion: There was no significant difference in knowledge about the prevention and transmission of Covid-19 before and after counseling. However, there are significant differences in knowledge about early detection, symptoms, and status of Covid-19 patients before and after counseling.